Reinterpretación y lectura contemporánea de los íconos gráficos de las fiestas del inti raymi de Salcedo, enfocada en la figura del danzante - Jami Alomoto, Hugo Alberto (2016)
Salcedo canton is a noble, hospitable land, with great cultural and traditional wealth, currently in process of devaluation due to the effects of globalization. For this reason, it is proposed to carry out the design of graphical icons based on the clothing of “Danzante de Salcedo”, to there by revalue the cultural identity of the sector and to inform the population the meaning of the icons that make up the clothing of this important character of the festival of “Inti Raymi Salcedo”. For the development of this project, we worked together with the people of the region and the author of the book "Los Danzantes del Inti Raymi: identity traits," Dr. Wilmo Gualpa to gather information about these celebrations. From literature and field research, the relevance of this research project focused on the figure of Danzante and his clothing was defined. With the information gathered, we proceeded to the development of the project, where they intervened knowledge gained throughout the race Computerized Graphic Design; the removal of the icons of the clothing of Danzante was a methodological and systematic process, it was taken reference the author's proposal Bruno Munari, which proposes several steps to get modules, took also postulates Wucius Wong contributed the generation of the composition of graphic elements, then this was done extracting graphical icons. The digitization process performed it was made using specialized software design, through a process of composition and geometrization to get textures were combined with 3D tools, and thus got digital replicas of handicrafts, with these replicas were carried out development of two brochures, applying corporate design tools. The final product was the result of a contemporary reading of the icons of the clothing of “Danzante de Salcedo”, presented in brochures, for use in handicrafts.